An Elementary Introduction to Kalman Filtering. - YAN PEI; BISWAS, SWARNENDU; FUSSELL, DONALD S.; PINGALI, KESHAV (Communications of the ACM, 2019)
The article offers derivation of Kalman filtering, a state estimation technique used in computer programming. Topics covered include computer system control, the use of Kalman filtering as a black box, and how Kalman filtering can improve approximation.